Rhodamine scaffolds as real time chemosensors for selective detection of bisulfite in aqueous medium. Issue 6 (26th March 2019) - Roy, Sumit; Maity, Ashim; Mudi, Naren; Shyamal, Milan; Misra, Ajay
Abstract : Rhodamine and its derivatives have been widely used in designing fluorescent 'turn on' cation sensors, while very few rhodamine based fluorescent probes have been reported to date for the detection of anions in water. Abstract : Rhodamine and its derivatives have been widely used in designing fluorescent 'turn on' cation sensors, while very few rhodamine based fluorescent probes have been reported to date for the detection of anions in water. In this article, a new rhodamine based facile and convenient 'turn on' fluorescent chemosensor 2-(2-(1-hydroxynaphthyllideneamino)ethyl)-3′, 6′-bis(diethylamino)spiro [isoindoline-1, 9′-xanthen]-3-one (RAHN) has been developed by Schiff base condensation and characterized by standard techniques for selective detection of bisulfite anions in water. A faintly yellow colour solution of RAHN turns pink upon addition of bisulfite. Again RAHN is weakly emissive in solution but becomes strongly emissive on addition of bisulfite and the emission intensity increases gradually in the presence of increasing concentration of bisulfite. No other analytes can cause emission enhancement of RAHN, suggesting the selectivity of the probe towards bisulfite. The detection limit for bisulfite was found to be ∼0.4 μM.